Teach About U.S. Moodle Course: The U.S. Embassy School Election Project 2012 - Kaliampos, Joannis; Schmidt, Torben; Kohl, Martina; Ernst, Karin; Krüger, Katja (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2023)
The resource comprises an English language course centered around the topic of U.S. 2012 Elections, encompassing a well-structured curriculum comprising language activities and multimedia resources, which can be seamlessly integrated into the Moodle learning management system. The course is structured around the theme of U.S. Presidential Elections, guiding students to explore and analyze a specific U.S. state in depth. Through intensive research and investigation, students delve into various aspects of the chosen state, including its voting history, economy, culture, demographics and political landscape. This comprehensive exploration empowers learners to develop a nuanced understanding of the state's unique characteristics and its potential voting patterns. Within the course, a wide range of engaging language activities is provided, encompassing reading comprehension, speaking opportunities, research and writing assignments. These activities are strategically designed to reinforce English language proficiency while simultaneously fostering critical thinking skills, cultural awareness, and deeper understanding of the U.S. political system. The inclusion of open source texts and materials enriches the learning experience and exposes students to authentic and diverse sources of information such as news articles, transcribed speeches, interviews, H5P videos, official government websites and historical documents related to U.S. Elections and politics. This exposure enhances learners' language proficiency by immersing them in real-world language usage and providing valuable insights into the intricacies of American politics. The course materials are conveniently packaged in a Moodle file.
Analysis of digital content
Other
Moodle file
Keywords: Englisch; Sprachenlernen; Computerunterstütztes Lernen; Digitales Lernen; Politische Bildung; Wahlen; Demokratie; Englischunterricht; Unterrichtsmaterial; Lernsoftware; E-Learning; Fremdsprachenerwerb; Interkulturelles Lernen; Sprachkompetenz; Politisches Bewusstsein; Interkulturelle Kompetenz; Blended Learning; English; Foreign Language; Language Learning; Computer-assisted Learning; Digital Learning; Political Education; Elections; Democracy; English Lessons; Teaching Material; Learning Software; E-Learning; Intercultural Learning; Language Competence; Political Awareness; Intercultural Competence; Blended Learning